Blood-letting puncturing combined with cupping therapy and nursing for the treatment of pain in a patient with stagnation of Liver-Qi and phlegm of hyperplasia of mammary glands (刺络放血拔罐治疗1例肝郁痰凝型乳腺增生患者疼痛的护理体会) - SUN Pengcheng (孙鹏程); LIU Cui (刘翠); TANG Ling (唐玲); CHEN Hong (陈宏) (中西医结合护理)
This paper summarized the effect of blood-letting puncturing combined with cupping therapy and nursing for the treatment of pain in a patient with stagnation of Liver-Qi and phlegm of hyperplasia of mammary glands. In addition to the nursing risk assessment and routine care, the blood-letting puncturing combined with cupping therapy was carried out based on the Traditional Chinese Medicine syndrome differentiation. The blood-letting puncturing combined with cupping therapy was proved to be effective in relieving the breast pain induced by mammary glands. (本文总结1例乳腺增生患者行刺络放血拔罐中医治疗的护理经验。患者入院后完善护理评估和常规护理, 基于中医辨证理论, 采取刺络放血拔罐干预, 能够有效缓解患者乳腺增生引起的乳房疼痛。)